2013
DOI: 10.1186/1753-2000-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Identity development in adolescents with mental problems

Abstract: BackgroundIn the revision of the Diagnostic and Statistical Manual (DSM-5), “Identity” is an essential diagnostic criterion for personality disorders (self-related personality functioning) in the alternative approach to the diagnosis of personality disorders in Section III of DSM-5. Integrating a broad range of established identity concepts, AIDA (Assessment of Identity Development in Adolescence) is a new questionnaire to assess pathology-related identity development in healthy and disturbed adolescents aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
8
34
2
3
Order By: Relevance
“…Patients with internalising disorders (anxiety and depression) scored slightly above the population norm, which may be interpreted as the presence of a current identity crisis. Patients with externalising disorders (ADHD and conduct disorder) did not differ from the school population in their identity development (29). It is in line with the AIDA definition of pathology-related identity development that patients with a personality disorder, especially borderline, show elevated scores, indicating that identity diffusion as defined in the AIDA…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Patients with internalising disorders (anxiety and depression) scored slightly above the population norm, which may be interpreted as the presence of a current identity crisis. Patients with externalising disorders (ADHD and conduct disorder) did not differ from the school population in their identity development (29). It is in line with the AIDA definition of pathology-related identity development that patients with a personality disorder, especially borderline, show elevated scores, indicating that identity diffusion as defined in the AIDA…”
Section: Discussionsupporting
confidence: 63%
“…Jung et al (29) examined differences in identity development between adolescents with different psychiatric disorders using the AIDA questionnaire (30,31). Jung et al (29) found that patients with personality disorders, mostly borderline or other B cluster personality disorders scored on all AIDA scales remarkably higher than the healthy norm population, and higher than the other patient groups with internalising or externalising disorders. Patients with internalising disorders (anxiety and depression) scored slightly above the population norm, which may be interpreted as the presence of a current identity crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The total score differentiated significantly between controls and patients with personality disorders, with effect sizes of more than two standard deviations (13).…”
Section: Continuity/discontinuity and Coherence/incoherencementioning
confidence: 91%
“…En el área infanto adolescente, en el año 2012, se publicó el cuestionario AIDA (Evaluación del Desarrollo de la Identidad en la Adolescencia), este instrumento de alta especificidad ha sido desarrollado para evaluar a menores de edad, entre los 12 y 18 años 30,31 . Según el director de la Clasificación de los Trastornos Mentales y del comportamiento de la Clasificación Internacional de Enfermedades (CIE-11) Geoffrey M. Reed, en la futura edición, el área de los trastornos de personalidad presentará cambios relevantes, con posibles énfasis en la severidad del trastorno y una nueva codificación de los rasgos más prominentes, pretendiendo lograr mejor utilidad clínica 32 .…”
Section: Comunicación Emocional Interna Y Con Losunclassified